2010
DOI: 10.3945/ajcn.2009.28813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soy protein and isoflavones on glycemic control and insulin sensitivity: a 6-mo double-blind, randomized, placebo-controlled trial in postmenopausal Chinese women with prediabetes or untreated early diabetes

Abstract: This 6-mo randomized controlled trial did not support the hypothesis that soy protein with or without isoflavone supplementation had favorable effects on glycemic control and insulin sensitivity among postmenopausal Chinese women. The favorable change in postload glucose needs to be further confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 30 publications
1
45
0
8
Order By: Relevance
“…Recently, Liu et al reported that SP with or without isoflavone did not have favorable effects on glycemic control and insulin sensitivity, even though BW was not changed at 6 months among Chinese women in a randomized, placebo-controlled trial. 22 These data indicate that formula food containing MP is superior to the same food containing SP for reducing visceral fat.…”
Section: Formula Food With Soy Protein Vs Milk Proteinmentioning
confidence: 69%
“…Recently, Liu et al reported that SP with or without isoflavone did not have favorable effects on glycemic control and insulin sensitivity, even though BW was not changed at 6 months among Chinese women in a randomized, placebo-controlled trial. 22 These data indicate that formula food containing MP is superior to the same food containing SP for reducing visceral fat.…”
Section: Formula Food With Soy Protein Vs Milk Proteinmentioning
confidence: 69%
“…An RCT conducted on 180 postmenopausal women with prediabetes or early untreated diabetes, treated with soy protein with or without isoflavone supplementation for 6 months, did not find any evidence of favorable effects on glycemic control and insulin sensitivity [142].…”
Section: Soy Isoflavonesmentioning
confidence: 99%
“…However, others showed no significant effect of soya protein (27)(28)(29) and soya isoflavone (27,30,31) . The results of an experimental study suggested that soyabean protein has the potential to improve insulin resistance or ameliorate obesity by inhibiting lipogenesis and promoting lipolysis in the liver and adipose cells (32) .…”
Section: Discussionmentioning
confidence: 99%